: Determinantes de la exportación agrícola del Ecuador. Periodo 2000-2020 - Garcia Tene, Laura Lisseth (2023)
ABSTRACT: The objective of this research is to identify the most significant factors that determine exports in the agricultural sector of Ecuador during the period 2000-2020, by applying the OLS multiple linear regression model. The theory analyzed recommends important variables for such analysis such as: agricultural GDP, trade openness and producer price index. The results found when applying the OLS were that the variables are significant, that is to say that these variables do influence the behavior of Ecuador's agricultural exports. In addition, the Johansen method was applied to corroborate the long-term relationship between the variables and it can be concluded that there is a long-term relationship between the variables in the model. Keywords: Agricultural exports, determinants, Ecuador and OLS.